The effects of Malaysian hotels services on customer loyalty. - Keshavarz, Yousef; Nezakati, Hossein * (2013)
In recent years, the tourism industry has become more important in terms of the global economy. It is revealed that inbound tourism has become one of the major trade categories. Like other countries in Malaysia several industries involve to attract tourists in the country. The hotel industry is one of these industries affects tourists to be satisfied and desire to visit the place again. Service quality is the most important factor by which hotels influence their guests to be loyal; therefore in this study the effect of service quality on tourist loyalty will be investigated. Factors of service quality, which affected from the expected service quality and affect tourist loyalty, include tangible, reliability, responsiveness, assurance and empathy. In this study, guests of hotels, apartments and budget hotels are considered as the research population and 500 respondents from both domestic and international tourists are selected by clustering sampling. The finding of this study is helpful for hoteliers to understand the demands of their customer from different countries with different cultures and plan new strategies to meet their needs and influence them to be loyal on hotels.